1999
DOI: 10.1016/s0741-5214(99)70129-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of screening on the incidence of ruptured abdominal aortic aneurysms

Abstract: Screening for asymptomatic AAAs can reduce the incidence rate of RAAAs by 49% (95% CI, 3% - 74%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(95 citation statements)
references
References 13 publications
1
94
0
Order By: Relevance
“…Evidence suggests that screening patients for AAAs resulted in an Ϸ45% reduction in the incidence of ruptured AAA 16,18 and a 21% to 68% decrease in aneurysmrelated deaths. 13,15,16,18,31 These observations have led a group of experts to recommend screening of AAA for all men 60 to 85 years of age, all women 60 to 85 years of age with cardiovascular risk factors, and all men and women Ͼ50 years of age with a family history of AAA. 19 The primary goal in AAA treatment is to prolong survival through the prevention of rupture.…”
Section: Ase Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that screening patients for AAAs resulted in an Ϸ45% reduction in the incidence of ruptured AAA 16,18 and a 21% to 68% decrease in aneurysmrelated deaths. 13,15,16,18,31 These observations have led a group of experts to recommend screening of AAA for all men 60 to 85 years of age, all women 60 to 85 years of age with cardiovascular risk factors, and all men and women Ͼ50 years of age with a family history of AAA. 19 The primary goal in AAA treatment is to prolong survival through the prevention of rupture.…”
Section: Ase Presentationmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Therefore, detection of AAAs before rupture and elective repair can prolong survival and decrease the periprocedural complication rate. Evidence suggests that screening patients for AAAs resulted in an Ϸ45% reduction in the incidence of ruptured AAA 16,18 and a 21% to 68% decrease in aneurysmrelated deaths. 13,15,16,18,31 These observations have led a group of experts to recommend screening of AAA for all men 60 to 85 years of age, all women 60 to 85 years of age with cardiovascular risk factors, and all men and women Ͼ50 years of age with a family history of AAA.…”
mentioning
confidence: 99%
“…1,13) Several studies reported a coexistence of atherosclerosis or disturbed connective tissue metabolism with AAA as an underlying etiology, 1,2,14) but the evidence for the role of lipids in the development of an AAA remains to be controversial. [15][16][17] Hobbs et al reported the highly significant association between LDL-C and small AAA, and LDL-C could be an initiating factor in the development of an AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the influence of various biomechanical factors, the growing aneurysm can potentially rupture that leads to either a neurological disorder or death. About 80% to 90% of ruptured aneurysms lead to death [1]. One of the invasive treatments for intracranial saccular aneurysms is to employ surgical procedures which may be associated with risk and death [2].…”
Section: Introductionmentioning
confidence: 99%